Robert J. Donia, Karadžić. Rzeźnik Bośni, Prószyński i S-ka, Warszawa 2023, ss. 480 (Tabularium Historiae, 2025)
Recenzja publikacji: Robert J. Donia, Karadžić. Rzeźnik Bośni, Prószyński i S-ka, Warszawa 2023.